Preferences of young physicians at community hospitals regarding academic research training through graduate school: a cross-sectional research. (December 2016) - Kurita, Noriaki; Murakami, Minoru; Shimizu, Sayaka; Kumasawa, Junji; Azuma, Teruhisa; Kataoka, Yuki; Yamamoto, Shungo; Fukuma, Shingo; Yamamoto, Yosuke; Fukuhara, Shunichi
Abstract Background Desire to attend graduate school for academic research training following the mandatory two-year clinical internship is unknown among young Japanese physicians who work at community hospitals after their internship. The aim of this study is to determine opinions and factors regarding pursuing higher education through graduate school among young physicians who work at community hospitals after their two-year internship. Methods This cross-sectional survey was conducted among young physicians working at community hospitals after their two-year internship. We examined the percentage of young physicians considering higher education through graduate school, the planned timing and field of enrollment among those wanting to enroll, and reasons for not continuing their education among those with no such plans. The association between desire to enroll in graduate school and background characteristics was examined using modified least-squares regression to estimate proportion difference. Results Among 127 (73.2 % internal medicine specialists, median age 30 years) physicians in 33 hospitals, 71 (55.9 %) stated that they wished to enroll in graduate school. The most frequently reported timing was 7–8 years after graduation from medical school. Those who stated no desire to attend graduate school cited concerns about the quality of training or not having enough knowledge to choose an appropriate laboratory or field, among other reasons. Increased number of years since graduating medical school [adjusted proportion difference (PD) −6.0 %, 95 % confidence interval (95 % CI) −9.8 to −2.3 %], being a woman with children [adjusted PD −53.4 %, 95 % CI −87.3 to −19.5 % (vs. a man not having children)], and completing their two-year internship at both university and community hospitals [adjusted PD −40.3 %, 95 % CI −72.5 to −8.0 % (vs. internship only at community hospitals)] were associated with a reduction in desire to enroll in graduate school. Conclusions We identified a growing trend in desire among young physicians to attend graduate school. Attracting those young physicians who express no desire to attend graduate school, however, will require establishment of more flexible graduate school programs which address their concerns.